Use of Sindbis virus-mediated RNA interference to demonstrate a conserved role of Broad-Complex in insect metamorphosis - Uhlirova, Mirka; Foy, Brian D; Beaty, Barry J; Olson, Ken E; Riddiford, Lynn M; Jindra, Marek (Proceedings of the National Academy of Sciences of the United States of America, 2003)
The transcription factor Broad-Complex (BR-C) is required for differentiation of adult structures as well as for the programmed death of obsolete larval organs during metamorphosis of the fruit fly Drosophila melanogaster. Whether BR-C has a similar role in other holometabolous insects could not be proven without a loss-of-function genetic test, performed in a non-drosophilid species. Here we use a recombinant Sindbis virus as a tool to silence BR-C expression in the silkmoth Bombyx mori. The virus expressing a BR-C antisense RNA fragment reduced endogenous BR-C mRNA levels in infected tissues (adult wing and leg primordia) via RNA interference (RNAi). The RNAi knock-down of BR-C resulted in the failure of animals to complete the larval-pupal transition or in later morphogenetic defects, including differentiation of adult compound eyes, legs, and wings from their larval progenitors. BR-C RNAi also perturbed the programmed cell death of larval silk glands. These developmental defects correspond to loss-of-function phenotypes of BR-C Drosophila mutants in both the morphogenetic and degenerative aspects, suggesting that the critical role of BR-C in metamorphosis is evolutionarily conserved. We also demonstrate that the Sindbis virus is a useful vehicle for silencing of developmental genes in new insect models.
Keywords: RNA, Viral; Drosophila melanogaster; Drosophila Proteins; sekvence nukleotidů; RNA virová; proteiny Drosophily; Bombyx; Cercopithecus aethiops; virus Sindbis; Eye; Pupa; molekulární sekvence - údaje; Sindbis Virus; DNA Primers; Chlorocebus aethiops; RNA, Small Interfering; kukla; Cricetinae; Metamorphosis, Biological; larva; Animals; Transcription Factors; oči; transkripční faktory; malá interferující RNA; zvířata; Culicidae; DNA primery; Vero Cells; Molecular Sequence Data; Base Sequence; Larva; Vero buňky; biologická proměna; křečci praví; bourec